ASAS PERADILAN SEDERHANA, CEPAT, DAN BIAYA RINGAN DALAM KETENTUAN PERSIDANGAN HYBRID PERKARA PERDATA - Syarif, Zulfadin (LPPM STIH Awang Long, 2024)
The aim of this research is entitled Principles of Simple, Fast and Low Cost Justice in Hybrid Trial Provisions for Civil Cases. The type of research that the author uses is normative legal research. The approach in this research uses a statutory approach and a conceptual approach. The research results obtained are: Firstly, in general hybrid trials are a modernization of trial procedures by utilizing digital technology, but for certain evidentiary stages it still refers to the conventional trial arrangements that apply, this raises the question of why comprehensive arrangements are not carried out, it is very important to ensure that hybrid trials are held in accordance with the principles of simple, fast and low-cost justice. Failure to do so could result in serious legal consequences and reduce public confidence in the justice system. Second, in relation to the position of statutory regulations that are recognized for their existence and have binding legal force but are outside the hierarchy, this will of course affect the smooth running of the justice system and will affect the efficiency, effectiveness and productivity of the judiciary itself. So, to ensure this, there needs to be clarity regarding the position of the Supreme Court Regulations in the hierarchy to avoid overlapping between legal regulations whose types are recognized in the law. Clarity regarding this position also influences regulatory products that will be issued between institutions or bodies that have the same authority in making laws and regulations, so that legal certainty is realized in the context of accommodating so many types of positive regulations and their regulations.